Redescription of late-instar larva of Scydmoraphes sparshalli (Denny) Coleoptera: Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2015)
The larva of Scydmoraphes sparshalli is redescribed. This is the first complete description of an immature Scydmoraphes with special focus on the chaetotaxic characters. The larva is unique among Cyrtoscydmini in having three pairs of stemmata, a very long sensory appendage of the antennomere II, mandibles with mesal row of microserrations interrupted by smooth portion of mandibular margin; maxillary mala with asetose apex and a row of very long, modified setae on mesal margin, and extremely elongate maxillary palpomere III and labium. A comparative study of previous descriptions resulted in recognizing a misidentification of a Scydmoraphes larva (the "Typ 2-Larve" of Schmid) as a putative Neuraphes (Pararaphes). The serial homology of chaetotaxic structures in the larva of Scydmoraphes sparshalli is discussed, and comparative notes on the larvae of Scydmoraphes, Neuraphes and Stenichnus are given, with an identification key.